An eye movement pre-training fosters the comprehension of processes and functions in technical systems - Skuballa, Irene T.; Fortunski, Caroline; Renkl, Alexander (Frontiers in Psychology, 2015)
The main research goal of the present study was to investigate in how far pre-training eye movements can promote knowledge acquisition in multimedia (pre-training principle). We combined considerations from research on eye movement modeling and pre-training to design and test a non-verbal eye movement-based pre-training. Participants in the experimental condition watched an animated circle which moved in close spatial resemblance to a to-be-learned learning environment, namely a static visualization of a solar plant accompanied by a narration. This training was expected to foster top-down processes as reflected in gaze behavior during the learning process and better knowledge. We compared two groups (N = 45): participants in the experimental condition received such pre-training in a first step and processed the learning material in a second step, whereas the control underwent the second step without any pre-training. The pre-training group outperformed the no-training group in their learning outcomes, particularly in knowledge about the processes and functions of the solar plant. However, the superior learning outcomes in the pre-training group could not be explained by eye-movement patterns. Furthermore, the pre-training moderated the relationship between experienced stress and learning outcomes. In the control group, high stress levels hindered learning, which was not found for the pre-training group. On a delayed posttest participants were requested to draw a picture of the learning content. Despite a non-significant effect of training on the quality of drawings, the pre-training showed associations between learning outcomes at the first testing time and process-related aspects in the quality of their drawings. Overall, non-verbal pre-training is a successful instructional intervention to promote learning processes in novices although these processes did not directly reflect in the learners’ eye movement behavior during learning.